Health Communication of the Public Health Ministry: the Case Study of the Coronavirus Disease 2019 (COVID-19) Pandemic - จันทร์เหมือน เยาวภา (Journal of Health Science of Thailand, 2022)
The objectives of this research were to study the Ministry of Public Health’s health communication information administration and to identify the Ministry’s health communication format for the case study of the Coronavirus disease 2019 (COVID-19) pandemics. This qualitative research methodology tools were the documentary analysis and the in-depth interview. The content areas of the documentary analysis were Coronavirus disease 2019 pandemics health communication, the related news and the summary of public-relations activities. In-depth interviews were conducted with 19 responsible and involved respondents. The data were collected between January 2020 and March 2022. The inductive conclusions were processed from the important-issues data according to research objectives. It was found that (1) there was the Public Health Emergency Operation Center (PHEOC) established for the administration of the Public Health Ministry’s health communication information, executed by the Risk Communication and Public Relations Mission Working Group. The center had responsibilities for monitoring all channel media information and evaluating the public awareness to provide press releases and talking points through various channels including media production for creating knowledge and understanding among the people. The main sources of information were the Global Initiative on Sharing All Influenza Data (GISAID), the World Health Organization (WHO) and the coronavirus disease 2019 experts; (2) the Ministry of Public Health has integrated all communication and public relations channels for the health communication format, according to the crisis plan. The format issues were determined into two components: (1) the epidemics situation, and (2) the health knowledge, the health behaviors, and personal hygiene for the prevention and the treatment for COVID-19. The results of this study suggest that Ministry of Public Health should formulate the epidemic risk communication executive plan covering both operational plans and budget plans to handle future outbreak situations and the fast and enormous information.